Ageing Eastwood Between Films and Media - Menarini, Roy (Mediascapes journal, 2025)
This article aims at analysing the last years of Clint Eastwood's artistic production and, at the same time, the physical ageing processes of the film star, as witnessed by images and photos that circulated on the Internet between his 93rd and 94th birthdays. Thanks to this case study, we can identify more clearly some aspects hidden by media rumors: the ambivalent relationship between on-screen and off-screen; the differences that are now imposed between the third and fourth age in storytelling and media representation; the negotiation of Eastwood's masculinity and his role as a male star; the clear difference between the artistic longevity of film directors depending on whether they are men or women.